OP0003 Rheumatic immune related adverse events of checkpoint therapy for cancer: case series of an emerging nosologic entity. (15th June 2017) - Calabrese, C; Kirchner, E; Kontzias, A; Velcheti, V; Calabrese, L
Abstract : Background: Immune checkpoint therapy is a major advance in the field of oncology. Agents targeting CTLA-4, programmed cell death protein 1 (PD-1) and PD-ligand 1 have produced significant survival benefits in patients with malignancies. With these therapies have come a unique spectrum of adverse events related to over-activation of the immune system with resultant autoimmune disease. To date reports of rheumatic immune related AEs (irAEs) have not been adequately characterized, as they are infrequently reported in clinical trials. We describe the largest series of rheumatic irAEs secondary to checkpoint inhibitors to date. Objectives: To report our 22 month experience with 19 patients evaluated in the Cleveland Clinic Rheumatology department. Methods: A retrospective chart review was performed on 19 patients, 16 without pre-existing autoimmune disease (AID) and 3 with pre-existing AID, seen in our rheumatology department February 2015-December 2016. 2 designated rheumatologists evaluated all patients. Recorded information included gender, age, age at malignancy diagnosis, malignancy details, checkpoint inhibitor, nature of rheumatic irAE, time of onset, diagnostic data, treatment of irAE and response to treatment. Results: In the group without pre-existing AID 56% developed a rheumatic irAE within 16 weeks of starting immunotherapy, with median time to onset of 14.5 weeks (table 1 ). Of the 3 patients with pre-existing AID, 1 experienced a disease flare after starting immunotherapy. Conclusions: Rheumatic irAEs is a new field that will continue to grow. At this stage we have more questions than answers regarding their epidemiology, natural history and pathophysiology. Our findings reinforce that rheumatic irAEs are complex, at times require aggressive immunosuppression and can impact checkpoint inhibitor therapy for the underlying malignancy. Disclosure of Interest: C. Calabrese: None declared, E. Kirchner: None declared, A. Kontzias: None declared, V. Velcheti Grant/research support from: Genentech, Bristol-Myers Squibb, Merck, Astra Zeneca, Genoptix, Consultant for: Genentech, Bristol-Myers Squibb, Merck, Astra Zeneca, Celgene, Genoptix, Foundation Medicine, L. Calabrese Consultant for: Bristol-Myers Squibb